(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The development of a methodological apparatus for the assessment and quantitative comparison of alternative innovations in the development of the agro-industrial complex (AIC) of Ukraine, especially the logistics system, is an urgent scientific task. The construction of a system of key performance indicators in this area, their implementation in the system of AIC standards will provide clear guidelines for enterprises and will allow the state to manage the development of the agricultural sector. In the article, based on the essence of the L8T-4 Bartini table, a transport service indicator is proposed for the system of loading (unloading) of container ships in the port, and the energy efficiency coefficient of this logistics operation is derived. An example of a numerical calculation for a specific seaport is given.